FINTECH INNOVATIONS AND THE TRANSFORMATION OF TRADITIONAL BANKS - Shokhzod Khujamurotov (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  In  this  article,  the  impact  of  fintech  innovations  on  the  traditional banking sector is analyzed. Fintech products, such as mobile payments, neobanks, and solutions  based  on  artificial  intelligence  (AI),  are  posing  new  challenges  to  banks' business models. The article examines types of fintech and their impact on banking services, as well as the adaptation strategies of traditional banks, which include digital transformation, investment in innovations, and open banking. Furthermore,  the  development  of  the  fintech  ecosystem  in  Uzbekistan  and changes in the local banking sector are analyzed. In conclusion, findings on future trends and the role of cooperation between banks and fintech in shaping the future of financial services are presented.